PENINGKATKAN KECERDASAN LOGIS-MATEMATIS ANAK USIA DINI MELALUI PERMAINAN PUZZLE ANGKA DI RAUDHATUL ATHFAL AR-RAHMAH - Widayanti, Ririn; Lubis, Hilda Zahra (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2024)
This research was conducted as a classroom action research at RA Ar-Rahmah Medan Estate Kec. Percut Sei Tuan North Sumatra Province which is applied to group B students. By playing number puzzles, the research carried out at RA Ar-Rahmah seeks and aims to improve students' mathematical logical abilities. There were 15 students from group B RA Ar-Rahmah Medan as the subjects of this research, 9 of whom were female and 6 of whom were male, participating in this research. Two learning cycles were applied to conduct this classroom action research. The research results showed that in general the pre-cycle was 60, in general the first cycle was 66.6, and in general the second cycle was 93.4. The findings of this research state that playing number puzzles regularly and substantially will increase the mathematical logical intelligence of students at Raudhatul Athfal Ar-Rahmah Medan Estate.